Peningkatan profesionalisme supeltas dalam pengaturan berlalu lintas di Wilayah Kecamatan Kartasura Kabupaten Sukoharjo - Suyahman, Suyahman; Rahayu, MH. Sri; CH, P. Andhi; Ermawan, Tegar; Putri, Anastasyia (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to investigate efforts to enhance the professionalism of Supeltas in traffic management in the Kartasura District, Sukoharjo Regency. In this research context, Supeltas' professionalism encompasses knowledge of traffic regulations, skills in handling field situations, and interpersonal communication abilities. The research method employed is a qualitative approach, involving in-depth interviews with several Supeltas and analysis of documentation related to professional training and development that has been conducted. The findings of this study will provide deeper insights into the factors influencing the professionalism of Supeltas in the area, as well as recommendations for improving their service quality. This research is expected to significantly contribute to efforts to enhance traffic safety and public service quality in Sukoharjo Regency specifically, and to contribute to the literature on traffic management at the local level.